A Core Chromatin Remodeling Factor Instructs Global Chromatin Signaling Through Multivalent Reading of Nucleosome Codes - Nair, Sujit S. (2013)
ATP-dependent NuRD repressor complexes involve combinatorial assembly of its subunits. However, the mechanism of gene transcription by MTA1/NuRD remains enigmatic. Here we report that MTA1 methylation by G9a methytransferase and demethylation by LSD1 determines the nucleosome remodeling and transcriptional outcome. Contrary to the current static repressor model of the NuRD complex, we discovered that MTA1 association with nucleosomes and co-repressor/ co-activator complexes is dynamic. While methylated MTA1 is required for the NuRD repressor complex, demethylated MTA1 recognizes the bivalent histone H3K4-AcK9 mark and recruits co-activator NURF-trithorax remodeling complex in a signaling-dependent manner. MTA1’s lysine 532 methylation represents a molecular switch as methylated and de-methylated MTA1 nucleate NuRD or NURF complexes with opposite functions in a cyclical manner. In addition, MTA1 possesses an inherent histone amplifier activity with an instructive role in impacting the epigenetic landscape, providing a new perspective to the molecular governance of dual co-regulator functions of a master coregulator.